Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) XVIII: One new species of Capnogryllacris and first reported female sex of Capnogryllacris xichou xichou Peng & Bian, 2021 - Zhang, Qianwen; Bian, Xun (Zootaxa, 2023)
Capnogryllacris is widely distributed in China, India, and Southeast Asia and contained 45 valid species. After examining the recently-collected specimens, we describe one new species and the female sex of Capnogryllacris xichou xichou Peng & Bian, 2021. All the new specimens are deposited in Guangxi Normal University.